Estado nutricional como factor de riesgo de preeclampsia en gestantes atendidas en el Hospital San Vicente de Paúl, en el periodo enero - julio del año 2022: Nutritional status as a risk factor for preeclampsia in pregnant women treated at the Hospital San Vicente de Paul, in the period January - July 2022 (La U Investiga, 2024)
Preeclampsia is the second cause of maternal death in the country after obstetric hemorrhage, for this reason the objective of this research is to analyze nutritional status as a risk factor for preeclampsia in pregnant women treated at the San Vicente de Paul hospital, in the period January - July 2022.The present investigation is retrospective, descriptive documentary with a quantitative approach and where a simple random statistical sampling was used to determine the sample size. 201 clinical histories were reviewed where different indicators such as ethnicity, age, weight, height, level of preeclampsia, type of delivery were taken into account. The results obtained were: average age of 26 years, predominant ethnicity: Afro-descendant, BMI >24.9 equivalent to overweight and obesity, diagnosis of preeclampsia if >140/90, when classifying the types of preeclampsia, 33 pregnant women presented mild preeclampsia and 34 pregnant women preeclampsia. severe at the same time, the type of delivery with the highest frequency was normal with a percentage of 49.8% of the selected sample and elective cesarean section being the type of delivery with the lowest percentage, having only 5.5%. It is concluded that obesity is a risk factor for preeclampsia in pregnant women treated at the San Vicente de Paul Hospital in the period January-July 2022, with these patients being twice as likely to develop this pathology.
Keywords: preeclampsia; overweight; obesity; body mass index; pregnant women